Psychiatric disorders among infertile men and women attending three infertility clinics in Riyadh, Saudi Arabia - Alosaimi, Fahad Dakheel (Ann Saudi Med, 2015)
BACKGROUND AND OBJECTIVES: No study has assessed psychiatric disorders among infertile men and women seeking fertility treatment in Saudi Arabia. Therefore, we sought to measure the rate of psychiatric disorders in this population. DESIGN AND SETTINGS: This was a cross-sectional observational study among patients attending infertility clinics at three referral hospitals in Riyadh, Saudi Arabia, between January 2013 and September 2014. PATIENTS AND METHODS: 406 patients (206 women and 200 men) participated in the study. The approved Arabic version of the MINI tool was used to assess 18 common psychiatric illnesses. RESULTS: The response rate was 81%. Of the men surveyed, only 4.5% self-reported having a psychiatric disorder. Of the women surveyed, only 10.2% reported having a psychiatric disorder. However, using the MINI scale, psychiatric illness was documented in 30% of males and 36.9% of females. The most common diagnoses for both genders were depression (21.7%) and anxiety (21.2%). Significantly more females than males exhibited suicidality and depression. In contrast, significantly more males than females had bipolar disorders and substance-related disorders. A low monthly income among male and female participants and polygamy among female participants were significantly associated with psychiatric disorders. CONCLUSIONS: This study shows that a higher prevalence of psychiatric disorders, particularly depression and anxiety, among infertile men and women in Saudi Arabia is associated with lower income and polygamy. This study highlights the importance of integrated care for alleviating the psychological burden of this unfortunate population and improving outcomes and quality of life. This study also encourages follow-up studies that aim to further understand the complex relationship between fertility and psychological well-being.